RACIAL DISCRIMINATION IN SHORT STORY CLARA (2014) BY SENO GUMIRA AJIDARMA - M.Radifan Arrafi; Muhammad Ilham; Nurul Fadhillah, (Proceeding of International Conference on Language Pedagogy (ICOLP), 2024)
Racial discrimination is a social phenomenon that is rooted in socio-psychological processes related to social cognition, group dynamics, and socialization among ordinary people. Seno Gumira Ajidarma's 2014 short story "Clara" explores the pervasive and widespread nature of racial prejudice and its disastrous effects on modern society. The story reveals the intricacies of discrimination that Clara experiences, ranging from unintentional slights to ingrained prejudices that affect the course of her life. This study employs Pieterse and Powell's (2016) postcolonial theory to identify examples of racism in the novel using descriptive and content analysis. In the final analysis, the writer aims not only to illuminate the deepest aspects of human nature and inspire us to take a more proactive, understanding, and empathic approach to combating racism, but also to draw parallels to the broader context of Indonesia and the world.